Integrative analysis of the metabolome and transcriptome provides insights into the mechanisms of flavonoid biosynthesis in blackberry. (March 2022) - Wu, Yaqiong; Zhang, Chunhong; Huang, Zhengjin; Lyu, Lianfei; Li, Weilin; Wu, Wenlong
Graphical abstract: Highlights: A comprehensive analysis of blackberry flavonoid biosynthesis and metabolism. Eight DEMs and 16 DEGs were annotated to flavonoid biosynthesis pathway. The study provides a reference for blackberry-related pharmaceutical industry. Abstract: Blackberry fruit is rich in anthocyanins, showing incomparable nutritional and health value. Anthocyanins are flavonoids that are downstream products of the flavonoid biosynthesis pathway. They are important secondary metabolites with antioxidant and anticancer functions. Therefore, we performed combined transcriptome and metabolome analyses of unripe and ripe blackberry fruits to identify the molecular mechanisms of flavonoid biosynthesis. Herein, we identified 997 differentially expressed metabolites (DEMs) in positive-ion mode, 411 DEMs in negative-ion mode, and 17, 566 differentially expressed genes (DEGs). Eight DEMs and 16 DEGs were annotated to the flavonoid biosynthesis pathway. Four DEGs related to flavonoids (unigene 0028088, unigene 0039337, unigene 0063209, and unigene 0014842) were positively correlated with related flavonoid DEMs. Interestingly, 8 DEGs and 11 flavonoid-related DEMs showed significant negative correlations. This study lays a foundation for further research on the biosynthesis and metabolism of flavonoid, providing a reference for the future breeding and cultivation of excellent high-flavonoid germplasm resources and the blackberry-related pharmaceutical industry.